Hubungan antara Dukungan Sosial dengan Optimisme pada Perantau Minang Survivor Kerusuhan Wamena - Nurvita Sari; Rina Mariana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between Social Support and Optimism in Minang Migrants survivors of the Wamena Riot. The independent variable in this study is social support and the dependent variable is optimism. Measuring instruments used in this research are social support scale and optimism scale. The sampling technique in this study uses saturated sampling technique. The sample in this study were 40 survivors of the Wamena riot who returned to their hometown with ACT (Fast Action Response) West Sumatra. The validity and reliability test in this study uses the Cronbach Alpha technique. The results of the validity coefficient on the scale of social support moves from rix = 0.358 to rix = 0.870 with a reliability coefficient of α = 0.930 while on the optimism scale moves from rix = 0.358 to rix = 0.870 with a reliability coefficient of α = 0.942. Based on data analysis, a correlation value of 0.563 was obtained with a significance level of 0.000, which means the hypothesis was accepted. This shows that there is a significant relationship between Social Support and Optimism on the Minang nomads survivors of the Wamena Riots